2023
DOI: 10.1186/s12957-023-02922-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of systematic lymph node dissection and influencing factors of sentinel lymph node biopsy using carbon nanoparticles in endometrial carcinoma: a single-center study

Abstract: Background Carbon nanoparticles (CNPs) are a new tracer for lymph node mapping, which can quickly reach and develop lymph nodes through a lymphatic network. This research investigated the characteristics of systematic lymph node dissection and sentinel lymph node biopsy mapped with CNPs in endometrial carcinoma. Methods We first applied CNPs to systematic lymph node dissection in 18 endometrial carcinoma patients as the study group and another 18 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…On the other hand, in the prospective study of Zao et al, which included 115 patients with endometrial cancer, unilateral and bilateral detection rates with carbon dye were 96.5% and 83.5%, respectively [ 13 ]. Recently, Tao et al conducted a study using carbon dye for SLNB in 54 patients with early-stage endometrial cancer, and the authors reported unilateral and bilateral detection rates as 70.4% and 40.7%, respectively [ 12 ]. In the present study, we calculated the unilateral and bilateral sentinel lymph node detection rates with carbon dye as 94.4% and 82%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the prospective study of Zao et al, which included 115 patients with endometrial cancer, unilateral and bilateral detection rates with carbon dye were 96.5% and 83.5%, respectively [ 13 ]. Recently, Tao et al conducted a study using carbon dye for SLNB in 54 patients with early-stage endometrial cancer, and the authors reported unilateral and bilateral detection rates as 70.4% and 40.7%, respectively [ 12 ]. In the present study, we calculated the unilateral and bilateral sentinel lymph node detection rates with carbon dye as 94.4% and 82%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, carbon dye has gained acceptance among general surgeons in SLNB procedures. The present study is one of the few studies using carbon dye alone as a tracer during the SLNB procedure in endometrial cancer [ 6 , 12 , 13 ]. Therefore, the objective of the present study was to evaluate the safety and efficacy of carbon dye for the detection of sentinel lymph nodes in endometrial cancer patients.…”
mentioning
confidence: 99%
“…Carbon nanoparticles are used in various fields, such as nanopharmacology, nanomedicine, and nanooncology, as they incorporate all the advantages of the nanotechnology industry, showing excellent absorption properties and the ability to aggregate [11]. Since the diagnosis and treatment of cancer are, at the moment, the most important problems in medicine, carbon nanoparticles have recently started to be used by surgeons in China for lymph node mapping in various operations carried out for malignancy, such as endometrial, breast, thyroid, gastric, and colorectal malignancies [12][13][14][15][16]. Carbon nanoparticles have been associated with an increased number of lymph nodes retrieved in surgery for the abovementioned malignancies, while they also improve the identification rate of small lymph nodes and can be used to trace sentinel lymph nodes in order to evaluate lymphatic metastasis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since the diagnosis and treatment of cancer are, at the moment, the most important problems in medicine, carbon nanoparticles have recently started to be used by surgeons in China for lymph node mapping in various operations carried out for malignancy, such as endometrial, breast, thyroid, gastric, and colorectal malignancies [12][13][14][15][16]. Carbon nanoparticles have been associated with an increased number of lymph nodes retrieved in surgery for the abovementioned malignancies, while they also improve the identification rate of small lymph nodes and can be used to trace sentinel lymph nodes in order to evaluate lymphatic metastasis [12,13]. Carbon nanoparticles have an average diameter of 150 nm and, as a result, can enter lymphatics that have a diameter of 120-500 nm and stain the lymph nodes black, but they cannot enter small blood capillaries (diameter of 20-50 nm), thus minimizing the adverse toxic effects [12,17].…”
Section: Introductionmentioning
confidence: 99%